2020
DOI: 10.1111/tgis.12704
|View full text |Cite
|
Sign up to set email alerts
|

“GIS works!”—But why, how, and for whom? Findings from a systematic review

Abstract: Systematic literature reviews have been a part of evidence-based practices for meta-analytical research in many disciplines, such as medicine, health science, psychology, and empirical social sciences, for decades.More recently, this approach has also gained interest in the field of education research (Zawacki-Richter, Kerres, Bedenlier, Bond, & Buntins, 2020). Review articles in geography and geoscience connected to educational inquiry are sparse. For example, Zadrozny, McClure, Lee, and Jo (2016) use a non-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 84 publications
(115 reference statements)
0
19
0
Order By: Relevance
“…Although previous studies have delineated how GIS contributes to fostering higher‐order thinking (Baker et al., 2015; Chen & Wang, 2015; Hong, 2017; Tan & Chen, 2015) and have elucidated the many advantages of utilizing GIS in cultivating advanced cognitive skills and abilities such as (geo)spatial thinking, problem‐solving, critical thinking, and analytical and evaluation skills (Collins, 2018; Favier & Van der Schee, 2012; Gonzalez & Torres, 2020; Schulze, 2021; Schulze et al., 2013; Sinton, 2012; Virranmäki et al., 2021), neither group in our study made significant gains in the challenging learning skills at level 4 (evaluate and create), resulting in almost equal performance between the two groups. The result lends credence to Van der Schee et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous studies have delineated how GIS contributes to fostering higher‐order thinking (Baker et al., 2015; Chen & Wang, 2015; Hong, 2017; Tan & Chen, 2015) and have elucidated the many advantages of utilizing GIS in cultivating advanced cognitive skills and abilities such as (geo)spatial thinking, problem‐solving, critical thinking, and analytical and evaluation skills (Collins, 2018; Favier & Van der Schee, 2012; Gonzalez & Torres, 2020; Schulze, 2021; Schulze et al., 2013; Sinton, 2012; Virranmäki et al., 2021), neither group in our study made significant gains in the challenging learning skills at level 4 (evaluate and create), resulting in almost equal performance between the two groups. The result lends credence to Van der Schee et al.…”
Section: Discussionmentioning
confidence: 99%
“…GIS is supportive of constructivist learning (Kerski et al., 2013; Kinniburgh, 2010), as it involves an interactive and constructive process to build maps and models that make sense of the world. Moreover, previous research has illuminated many benefits of GIS in geographical education (Bikar et al., 2022; Jo & Hong, 2020; Li et al., 2022; Liu et al., 2010; Phantuwongraj et al., 2021; Schulze, 2021), including (1) Enhancing thinking skills and knowledge: Geospatial technologies like GIS have demonstrated the potential to enhance student learning, spatial and critical thinking skills (Baker & White, 2003; Demirci, 2015; Goldstein & Alibrandi, 2013; Lee & Bednarz, 2009). Students exhibited greater gains in content knowledge when utilizing GIS‐related technology as compared to traditional methods (Metoyer & Bednarz, 2017); (2) Advancing spatial relationship understanding: GIS offers a more interactive and engaging learning experience conducive to advancing students' understanding of spatial relationships (Favier & Van der Schee, 2014); (3) Strengthening decision‐making and reasoning: The use of GIS in education has been linked to meaningful decision‐making and an enhanced reasoning about issues, such as climate change and air pollution (Cox et al., 2014; Hodza et al., 2021; Kerski, 2008; Miller, 2022; Milson et al., 2012; Milson & Kerski, 2012); (4) Enabling visualization for easier learning: GIS technology excels in visualizing spatial arrays, concepts, layouts, relations, trends, and processes.…”
Section: Introductionmentioning
confidence: 99%
“…Conceptual frameworks have been proposed to address the knowledge transfer challenges that GIS students face. A recent review of research studies about GIS instruction found that constructivist approaches help students develop technical competence through experiential, hands-on projects (Schulze, 2020). Howarth and Sinton (2011) propose a framework that sequences spatial concepts and combines problem-based learning with cognitive load theory to scaffold student learning.…”
Section: What Does a Gis Contain?mentioning
confidence: 99%
“…Collaboration between students is acknowledged to develop effective GIS teaching (Schulze, 2021); however, there is lack of research evidence on the how aspect. Collaboration on a geospatial software project usually requires team members to rely on a version control system (VCS).…”
Section: Introductionmentioning
confidence: 99%